Exploring the toxicity of the aged styrene-butadiene rubber microplastics to petroleum hydrocarbon-degrading bacteria under compound pollution system - Changrong Zhao (Elsevier, 2021)
As a new pollutant, microplastics have increasingly drawn public attention to its toxic behavior in the environment. The aim was to investigate the effect of styrene-butadiene-rubber microplastics (mSBR) with different degrees of aging on petroleum hydrocarbon (PHC) degrading bacteria in an environment with simultaneously existing pollutants. A series of experiments were carried out to investigate the changes in the physical and chemical properties of mSBR with aging and to examine the influence of these changes on the inhibition of PHC-degrading bacteria by mSBR in the vicinity of coexisting pollutants. The results showed that in the early stage of ultraviolet aging (10d), the particle surface shows wrinkles, but the structure is intact. After reaching the late stage of aging (20d), nano-scale fragments were generated on the surface of mSBR, the average particle size decreased from 3.074 µm to 2.297 µm, and the zeta potential increased from − 25.1 mV to − 33.1 mV. The inhibitory effect of bacteria is greater. At the same time, these changes in the physicochemical properties increase the adsorption effect of Cd by 20%, and also improve the stability of mSBR in solution, whereby bacterial growth is inhibited by inhibiting the LPO activity and protein concentration of PHC degrading bacteria.